INFLATION AND SUSTAINABLE DEVELOPMENT GOALS (SDG) IN NIGERIA - Abu, Silas Idoko; Idoko, Cletus Usman; Adama, Ibrahim Joseph (Economics and Statistics Research Journal (ESRJ), 2025)
This study examined the impact of inflation on sustainable development goals in Nigeria. The specific objectives of this study were to examine the impact of inflation, interest rates, and exchange rates on SDGs in Nigeria from 2000 to 2023. Annual time series data on the Human Development Index (HDI), Inflation rate (INF), exchange rate (EXT), and interest rate (INT) were sourced from the Central Bank of Nigeria (CBN) Statistical Bulletin, 2023 and National Bureau of Statistics (NBS) Publications for the year 2023. The Human Development Index (which was used as proxy to sustainable development goals) served as the dependent variable. The independent or explanatory variables of the study were INF, EXT, and INT. The study used the Autoregressive Distributive Lag (ARDL) econometric technique to achieve all the objectives, and the findings showed that inflation had the expected negative and significant impact on SDGs in the economy within the study period. Although interest rates had the expected inverse relationship with HDI, it was statistically insignificant. Furthermore, exchange rate had the unexpected direction of relationship with SDGs and was not statistically significant in influencing SDGs within the study period. Based on these findings, this study concludes that the inflation rate has the potential to adversely affect the attainment of the SDGs in Nigeria. Therefore, the study recommends that governments and policymakers take steps toward achieving price stability in the economy. The government and monetary authorities should equally ensure that interest rates positively impact SDGs by providing development funds available to concerned stakeholders at a subsidized rate of interest. This can take the form of concessions and establishing a special credit window for these crucial goals. Moreover, decreasing interest rates to stimulate domestic progress on the attainment of the SDGs will go a long way to increase the variety of domestic goods, which in the longrun is capable of generally lowering inflationary pressures in the economy.